An Approach for the Selective Detection of Nitric Oxide in Biological Systems: An in vitro and in vivo Perspective. Issue 7 (1st March 2016) - Gupta, Neha; Imam Reja, Shahi; Bhalla, Vandana; Gupta, Muskan; Kaur, Gurcharan; Kumar, Manoj
Abstract: A naphthalimide‐based fluorescent probe, LyNP‐NO, was designed and synthesized for the selective detection of exogenously and endogenously generated nitric oxide (NO) in C6 glial cells. In addition, LyNP‐NO was also explored for monitoring endogenous NO levels in rat hippocampus at various tissue depths by stimulating the brain with N ‐methyl‐d ‐aspartate (NMDA). Abstract : NO doubt : Naphthalimide‐based fluorescent probeLyNP‐NO selectively detected exogenously and endogenously generated nitric oxide (NO) in C6 glial cells.LyNP‐NO was also explored for monitoring endogenous NO levels in rat hippocampus at various tissue depths by stimulating the brain with N ‐methyl‐d ‐aspartate (NMDA).